2022
DOI: 10.7759/cureus.21715
|View full text |Cite
|
Sign up to set email alerts
|

Retro-Odontoid Intradural Synovial Cyst Decompression via Endoscopic-Assisted Far-Lateral Approach C1-C2 Hemilaminectomy Without Fusion: The Use of Intracranial Denticulate Ligament as Intraoperative Landmark

Abstract: Purely intradural retro-odontoid synovial cysts are rarely reported in neurosurgical literature, particularly in the absence of associated bony erosions. We present the case of a 57-year-old Native American male with a retro-odontoid synovial cyst and a history of chronic refractory neck pain that was adequately decompressed via an endoscopic-assisted far-lateral approach using a C1-2 hemilaminectomy, obviating the vertebral artery (VA) transposition, bony instability, and the need for instrumented bony fusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Forceful resection could lead to significant or permanent neurological complications given the proximity to critical structures. 13,14 Fortunately, in cases in which complete resection was not possible, significant improvement has been reported with partial resection/decompression and a low frequency of recurrence. 5,9,13 For our case, retromastoid craniectomy provided optimal exposure of the cyst.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forceful resection could lead to significant or permanent neurological complications given the proximity to critical structures. 13,14 Fortunately, in cases in which complete resection was not possible, significant improvement has been reported with partial resection/decompression and a low frequency of recurrence. 5,9,13 For our case, retromastoid craniectomy provided optimal exposure of the cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Of 43 articles found on the topic from 1988 to 2023, only 30 cases were relevant to the atlantoaxial/atlantooccipital junction and only 13 of these cases were treated with craniotomy/craniectomy and/or involved cranial nerve palsy (Table 1). [2][3][4][5][6][7][8][9][10][11][12][13][14] Articles were excluded if pathology was found to be anything other than synovial cyst, if the cyst was at a subaxial cervical level, or if either full text was unavailable or the abstract did not provide sufficient information for the literature review.…”
Section: Methods For Literature Reviewmentioning
confidence: 99%
“…In general, resection of the synovial cyst was using open or microsurgical surgery of hemilaminectomy or laminectomy with or without additional fusion. The majority of synovial cysts removal reported in the literature focused on the lumbar or cervicothoracic spine level [21] , [22] , [23] , [24] , [25] . As previous literature reports about the lumbar synovial cysts removal, the posterior endoscopic approach reduces the muscle denervation and decreases the risk of postoperative hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only 13 cases of intradural synovial cysts or ganglion cysts in the spinal canal have been reported previously (Table 1). [8][9][10][11][12][13][14][15][16][17][18] Among these 13 cases, two were located at the lower lumber spine, whereas the other 11 occurred at the craniovertebral junction (CVJ). None of the previous literatures noted this high frequency of dural penetration at the CVJ.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports have been published on "intradural synovial cysts" (IDSCs). [8][9][10][11][12][13][14][15][16][17][18][19] A review of these reports showed that dural penetration of the extradural cyst most frequently occurs at the craniovertebral junction. Neurological symptoms had been caused by direct compression of the spinal cord, brain stem, or hypoglossal nerve.…”
Section: Introductionmentioning
confidence: 99%